(untitled) (Journal of EAHIL, 2020)
The article describes a case study, using design thinking methods, to evidence base the renovation of two buildings on the university campus. The project involves several stake holders and is looking at the general study environment, and not only the library space. In the discussion the author compares the processes from evidence based library and information practice, design thinking methods and a hybrid model, as well as outlines some learning points from the project.